Biochemical and immunological characterization of polyproteins coded for by the McDonough, Gardner-Arnstein, and Snyder-Theilen strains of feline sarcoma virus. - Barbacid, M (1980)
The McDonough (SM), Gardner-Arnstein (GA), and Snyder-Theilen (ST) strains of feline sarcoma virus (FeSV) code for high-molecular-weight polyproteins that contain varying amounts of the amino-terminal region of the FeLV gag gene-coded precursor protein and a polypeptide(s) of an as yet undetermined nature. The SM-FeSV primary translational product is a 180,000-dalton polyprotein which is immediately processed into a highly unstable 60,000-dalton molecule containing the p15-p12-p30 fragment of the FeLV gag gene-coded precursor protein and a 120,000-dalton FeSV-specific polypeptide. The GA- and ST-FeSV genomes code for polyproteins of 95,000 and 85,000 daltons, respectively, which in addition to the amino-terminal moiety (p15-12 and a portion of p30) of the FeLV gag gene-coded precursor protein also contain FeSV-specific polypeptides. However, the GA- and ST-FeSV polyproteins appear to be relatively stable molecules (half-lives of around 16 h) and are not significantly processed into smaller polypeptides. Immunological and biochemical analysis of each of the above FeSV translational products revealed that the sarcoma-specific regions of the GA- and ST-FeSV polyproteins are antigenically cross-reactive and exhibit common methionine-containing peptides. These findings favor the concept that these sarcoma-specific polypeptides are coded for by the similar subsets of cellular sequences incorporated into the GA- and ST-FeSV genomes during the generation of these transforming agents.